2011
DOI: 10.1016/j.envexpbot.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of defence metabolites in tomato plants infected by the bacterial pathogen Pseudomonas syringae

Abstract: being associated with the tomato/P. syringae interaction. Inhibition of the P. syringaeinduced ethylene by 2-aminoethoxyvinylglycine, markedly impaired the accumulation of HCAA in inoculated tomato leaves, but it had no effect on CGA or rutin synthesis.On the other hand, the lack of accumulation of SA in NahG transgenic tomato plants, overexpressing a bacterial salicylic hydroxylase, did not prevent the enhancing of 40 HCAA produced by P. syringae infection. Taken together, our results indicate that ethylene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 62 publications
(69 reference statements)
2
71
1
Order By: Relevance
“…2). Infections caused by A. alternata have been shown to increase the content of phenolic acids in tomatoes (López-Gresa et al 2011;Wojciechowska et al 2014). Plants rapidly accumulate phenolic compounds in response to a pathogenic infection (Gogoi et al 2001).…”
Section: Severity Of Late Blight and Early Blightmentioning
confidence: 99%
“…2). Infections caused by A. alternata have been shown to increase the content of phenolic acids in tomatoes (López-Gresa et al 2011;Wojciechowska et al 2014). Plants rapidly accumulate phenolic compounds in response to a pathogenic infection (Gogoi et al 2001).…”
Section: Severity Of Late Blight and Early Blightmentioning
confidence: 99%
“…Citrus plants (12 months old, about 1 m height) were kept in temperature-controlled greenhouse (28)(29)(30)(31)(32) C) and were watered twice a week and fertilized once a week using 20-10-20 fertilizer (Allentown, PA). The thirteen different citrus varieties that were used in this study are shown in Table 1.…”
Section: Plantsmentioning
confidence: 99%
“…Traditionally, the analytical techniques employed in the search for these metabolites were basically chromatographic, coupled to spectroscopic detectors or mass spectrometers (Baumert et al, 2001;Shadle et al, 2003;Tan et al, 2004) . Accordingly, the range of metabolites that can be identified using 85 these techniques is restricted based on the case specific experimental procedures employed and the physical-chemical properties of the compounds investigated (Roepenack-Lahaye et al, 2003;Bednarek et al, 2005;Fayos et al, 2006;Zacarés et al, 2007;Bellés et al, 2008;López-Gresa et al, 2011). However, a considerable amount of biomolecules with different biological functions (and physical-chemical 90 properties), are proposed to be involved in the physiology of plant/pathogen interactions.…”
Section: Introductionmentioning
confidence: 99%